The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/1806-9061-2017-0542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Intensity on Growth, Anti-Stress Ability and Immune Function in Yellow Feathered Broilers

Abstract: An experiment was conducted to investigate the effects of light intensity on growth, anti-stress ability, and immune function of yellow feathered broilers. A total of 480 one-day-old male Lingnan yellow feathered broilers were randomly allocated to 4 treatments based on light intensity (1, 5, 20 and 80 lx) with 8 replicates of 15 chicks each. The experiment lasted for 63 days. Compared with those under high light intensity, broilers exposed to low light intensity had higher (p<0.05) total antioxidant capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Guo et al . [41] agreed with our findings; they found an improvement of a-Naphthyl-acetate esterase and increased antibody production in broilers exposed to intermediate or low-intensity blue lights for the increased melatonin or activation of T and B lymphocyte proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Guo et al . [41] agreed with our findings; they found an improvement of a-Naphthyl-acetate esterase and increased antibody production in broilers exposed to intermediate or low-intensity blue lights for the increased melatonin or activation of T and B lymphocyte proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…These results proved that broiler chickens were more sensitive to light intensity. Whereas, when boilers reared at low light intensity environment, they had a low level of stress and strong light is considered a stress factor in poultry production (Guo et al, 2018). Increased percentage of NDV antibody titer under dim blue light in this experiment suggested that low light intensity improved the cellular and humoral immune responses of broilers.…”
Section: Discussionmentioning
confidence: 67%
“…In the control group, the light intensity was 18 lux whereas in the experimental group, the light intensity was measured between 0 and 12 lux, below this value, in a large part of the house. Guo et al (2018) express that broilers under low light intensity might have similar performances. The findings of the study are consistent with this view.…”
Section: Resultsmentioning
confidence: 98%